Lessons learned from the underrepresentation of women in STEM: AI-enabled solutions and more - Abuwatfa, Waad Hussein (2021)
The absence of women in STEM and energy sectors is driven by discrimination and socio-cultural factors. A greater number of women “leak out” from Energy and STEM fields than men. AI-enabled solutions offer analysis tools to measure and evaluate diversity and inclusion.